Dictionary of erotic artists : painters, sculptors, printmakers, graphic designers, and illustrators - Burt, Eugene C., 1948- (McFarland & Co., 2010)
"This alphabetically arranged dictionary of artists known to have produced works depicting sexual imagery profiles the artists from ancient times to the present. Each entry offers biographical information, including the artist's name and any variants, birth and death dates, geographic focus, a description of the artist's media, training and the nature of their artistic output"--Anotace vydavatele
Terminologický slovník
Keywords: výtvarné umění; erotické náměty; výtvarní umělci; art; erotic themes; artists; biografické slovníky; biographical dictionaries